Curcumin Attenuates Zearalenone-Induced Reproductive Damage in Mice by Modulating the Gut Microbe–Testis Axis - Bangwang Peng; Shuaiju Guo; Junlong Niu; Yongpeng Guo; Zhixiang Wang; Wei Zhang (Foods)
Zearalenone (ZEN), a mycotoxin commonly found in cereal crops and foods, induces testicular damage and disrupts gut microbial composition. Curcumin (CUR), a bioactive compound derived from turmeric, is known to enhance intestinal microbial balance and exhibit anti-inflammatory properties. This study aimed to investigate the mechanism by which CUR alleviates ZEN-induced reductions in sperm quality through the modulation of the gut microbiota–testis axis. Forty-eight 6-week-old Balb/c male mice were randomly assigned to four treatment groups: control (CON), CUR (200 mg/kg body weight CUR), ZEN (40 mg/kg body weight ZEN), and ZEN + CUR (200 mg/kg CUR + 40 mg/kg ZEN). The degree of sperm damage was quantified by assessing both the survival rate and the morphological integrity of the spermatozoa. CUR was found to mitigate ZEN-induced reductions in the testosterone levels, testicular structural damage, and disrupted spermatogenesis. Exposure to ZEN markedly perturbed the gut microbiota, characterized by increased relative abundances of Prevotella and Bacteroides and a concomitant reduction in Lactobacillus. These alterations were accompanied by pronounced activation of the IL-17A–TNF-α signaling axis, as demonstrated by elevated transcriptional and translational expression of pathway-associated genes and proteins. Co-administration of CUR effectively reinstated microbial homeostasis and mitigated ZEN-induced IL-17A pathway activation. In conclusion, ZEN induces testicular inflammation and reduced sperm quality by lowering testosterone levels and disrupting gut microbial balance, which drives the testicular IL-17A signaling pathway. CUR alleviates ZEN-induced testicular inflammation and sperm quality reduction by restoring beneficial gut microbes and testosterone levels.